The role of peace education in promoting social justice and sustainable peace in post-conflict societies: a 4Rs framework analysis - Adan, Mohamed Yusuf (Frontiers in Political Science, 2025)
IntroductionThis study examines the role of peace education in promoting social justice and sustainable peace in post-conflict societies, with a specific focus on Somalia. Although Somalia lacks a formal peace education subject within its national curriculum, themes such as peace, tolerance, reconciliation, and civic responsibility are interwoven into existing subjects like Social Studies, History, Islamic Education, and Conflict Resolution at the university level. The study draws on the 4Rs framework, Redistribution, Recognition, Representation, and Reconciliation, to assess how education can address the root causes of conflict and social division.MethodsThe study employed a qualitative comparative case study approach, drawing on secondary data from Somalia, Rwanda, and Sierra Leone to assess how different post-conflict countries have integrated peace education into their national systems.ResultsFindings indicate that while Somalia has made efforts to integrate peace-related themes into education, its approach remains fragmented and lacks a unified strategy. Key challenges include disparities in access to education, limited inclusion of marginalized voices in curriculum development, and inadequate engagement with historical grievances. By contrast, Rwanda and Sierra Leone have implemented more structured and coordinated peace education initiatives that have contributed to national reconciliation and civic rebuilding.DiscussionThe study highlights the transformative potential of peace education in post-conflict contexts when anchored in a justice-oriented framework. Somalia’s current efforts, though commendable, require stronger policy coordination, broader stakeholder participation, and comprehensive curriculum reform to fully harness the role of education in sustaining peace.